Política de assistência estudantil na Universidade Federal da Paraíba e os critérios para concessão do auxílio Restaurante Universitário no Campus I - Silveira, Hélio Pereira da Mota (2019)
The purpose of this study was to analyze the selection process of the University Restaurant (RU) student aid in Campus I in order to understand if the criteria established in the Pro-Rectory's for Student Assistance and Promotion (PRAPE) edicts, in addition to the criteria National Program of Student Assistance (PNAES), were decisive in the final results. This is a documentary research with a qualitative approach to documentary analysis and quantitative data. The data analyzed refer to the relation between the demand for the mentioned aid, criteria established in the edicts, and the reasons for the declassifications in the selective processes for the granting of Campus I Universitarian Restaurant assistance. Data collection was done through the formalization of a process together with PRAPE, when the number of disqualified students was requested and the reasons for the disqualification of these students. The subjects of the research were the candidates who had the result rejected / not approved in the selective processes for granting the RU aid of the campus I, being established a sample of 10% to analyze the reasons for the disqualification. The theoretical basis was based on the concept of student assistance as a social policy and the focus of this policy. We also discussed the process of expansion of higher education in Brazil, the enrollment of students in situations of socioeconomic vulnerability and the PNAES as a policy of permanence and evidence aspects pertinent to student assistance in the UFPB. Analyzing the edicts, it was verified that PRAPE added criteria for access to benefits beyond those provided in the PNAES. In view of this, it was intended, based on the disqualification opinion, to recognize the applicability of the PRAPE criteria for the granting of aid and the dimensions of exclusion and thus to contribute to a more inclusive concession process. The research concluded that the criteria added by PRAPE had little relevance in the declassifications of RU aid applicants, since the reason "incomplete documentation" was the most significant responsible for declassifications.